Sistema de caracterização de depósitos sedimentares em função das respostas latentes acústica, elétrica e térmica - Laskoski, Gustavo Theodoro (2014)
This work describes overall integration of various sensors and geotechnical characterization of sediments. The techniques of analysis are typically characterized by in situ descriptions and laboratory techniques. Sometimes, laboratory responses cannot be explained by descriptions performed in situ, resulting in false positives and the necessity of new measurements. The proposal of a system that integrates sensors and geotechnical analysis in situ provides a better response due to results independent of researcher. Furthermore, the results will be provided in real time and some measurements errors can be easily detected. In this work, the developed system integrates responses of acoustic, electrical, and thermal sensors. The sensors were built in a plate of fiberglass and they are inserted into sediments. A first proposal is the evaluation of acoustic response. In this situation, two sensing plates separated by a given distance is used, where an electric signal is used to generates an acoustic signal and a piezoelectric crystal in the other sensor plate is used to detected received signal. The same setup was employed in a set of electrodes, where an electrical signal is applied into two electrodes arranged in two separate plates and the electrical impedance response is evaluated . Besides that, capacitive sensors are inserted into sediments to measure electrical impedance as a function of the characteristics of sedimentary deposit. Other developed system evaluates the thermal response. In this sensor, a set of resistors is used to heat the sediments and a set of thermistors is used to measure temperature variation. In this work, some tests were performed to evaluate the varition of sensors in situations of low and high degree of water saturation. In addition, it is presented the developed instrumentation. Based on the tests performed, developed system allows the measurement of water saturation based on the electrical and thermal responses. Besides that, laboratory tests show variations for different types of soil, where it can be used for soil classification. Furthermore, the system can be used in environmental monitoring, where solar irradiation, temperature, and soil moisture data can be evaluated.